2022
DOI: 10.1042/cs20210509
|View full text |Cite
|
Sign up to set email alerts
|

Emergent players in renovascular disease

Abstract: Renovascular disease (RVD) remains a common etiology of secondary hypertension. Recent clinical trials revealed unsatisfactory therapeutic outcomes of renal revascularization, leading to extensive investigation to unravel key pathophysiological mechanisms underlying irreversible functional loss and structural damage in the chronically ischemic kidney. Research studies identified complex interactions among various players, including inflammation, fibrosis, mitochondrial injury, cellular senescence, and microvas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 207 publications
0
4
0
Order By: Relevance
“…Renal artery stenosis (RAS), mainly caused by atherosclerosis ( 1 ), is a common etiology of renovascular hypertension (RVH) ( 2 ). RAS not only results in hemodynamic disorders and deteriorating renal function, but is also exacerbated by systemic diseases including metabolic syndrome (MetS) and diabetes mellitus ( 3 ). Conversely, all of these risk factors are crucial contributors to atherosclerosis ( 4 ) and cardiovascular disease (CVD) ( 5 ), a leading cause of death in the U.S ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Renal artery stenosis (RAS), mainly caused by atherosclerosis ( 1 ), is a common etiology of renovascular hypertension (RVH) ( 2 ). RAS not only results in hemodynamic disorders and deteriorating renal function, but is also exacerbated by systemic diseases including metabolic syndrome (MetS) and diabetes mellitus ( 3 ). Conversely, all of these risk factors are crucial contributors to atherosclerosis ( 4 ) and cardiovascular disease (CVD) ( 5 ), a leading cause of death in the U.S ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…In rats, circulating EVs have been shown to be able to suppress vasodilation [ 199 , 200 ] and thus play an important role in hypertension. Namely, it has been shown that hypertensive patients show an increase in EC-EVs in the plasma [ 201 ] and urine [ 202 ]. Thus, blocking the generation and release of EVs was found to reduce blood pressure in hypertensive rats [ 203 ].…”
Section: Biology Of Extracellular Vesiclesmentioning
confidence: 99%
“…Renovascular disease usually presents in two different clinical forms: Renovascular Hypertension, characterized by renal artery stenosis, systemic hypertension, and normal renal function; Ischemic Nephropathy, characterized by renal artery stenosis, increased intrarenal vascular resistance, and a decrease in renal function with or without hypertension [ 3 ]. Renal failure because of ischemic nephropathy results from functional, hormonal, and anatomical alterations induced by chronic renal hypoperfusion and ischemia [ 4 ]. Currently, the hypothesis that an increased intraparenchymal vascular resistance without renal artery stenosis may cause glomerular hypoperfusion and a decline in glomerular filtration rate towards ESRD, not associated with glomerular damage, has not been well defined [ 5 ].…”
Section: Introductionmentioning
confidence: 99%